Sentiment Analysis of Students’ Experiences during Online Learning in a State University in the Philippines - Santiago Jr., Cereneo S.; Centeno, Zarah Jane R.; Ulanday, Ma. Leah P.; Cahapin, Erwin L. (International Journal of Computing Sciences Research, 2023)
Purpose - This paper investigated the students’ opinions during online learning. Performing sentiment analysis (SA) of students’ experiences during online learning helps academic institutions and educators to understand their students, gauge their existing processes and delivery of instruction, and promote meaningful learning experiences from it. Method - The study utilized the sentiment analysis approach in obtaining the polarity, subjectivity, and presentation of visualization results. The student-respondents were conveniently chosen for they were available to answer the question using Google form. A total of 94 unstructured responses were retrieved, preprocessed, analyzed using sentiment analysis, and interpreted. Result - The result revealed that students’ opinion during online learning was dominated by positive experiences. The subjectivity of their sentiments was based on opinions. Further, it was found that the most frequent sentiments are positive, neutral, and negative attributes about “online”, “class”, “time”, “need”, “also” followed by “ internet”, “connection”, “study”, “learning”, and “struggle”. Conclusion - Students during online learning adapted new methods and approaches to learning despite some challenges. Their sentiments will guide educators to see the situation of learners from different perspectives and improve online teaching strategies to better serve the student-clienteles in cases such as emergency and remote or online learning. Recommendation – The research suggests that online learning can be successful if educational institutions, educators, and other stakeholders will work together in identifying and asserting the gaps, adapting the pedagogy of care, and filling the learners with the right learning resources and technology in ways that are meaningful and helpful. Implication – The overall students’ experiences during online learning in a state University in the Philippines will serve as a reference point for faculty and school administrators of other HEIS’ to look at how online teaching strategies can be tailored fit to the needs of the learners.